Therapeutic interventions employed when working with maltreated children - Sesar, Kristina, psihologinja (Array, 2021)
A number of effective treatments are available for children and young people who have developed various forms of psychological difficulties as a consequence of traumatic experiences. The aim of this paper is to review the therapeutic approaches employed when working with children who have been exposed to various forms of abuse and neglect during their childhood. This paper provides relevant information to psychotherapists and counsellors on new trends in therapy, as well as techniques and possibilities in interventions in this field, not only with respect to traumatised children, but also family members and other caregivers involved in the child’s life. Furthermore, this paper reviews the therapeutic interventions used to treat emotionally, sexually, and physically abused children, neglected children, children who have witnessed domestic violence, and children who have been exposed to multiple forms of abuse.